Monthly Mathematical Colloquium MMC 3, 2023 - Chuan, Zun Liang (Pusat Sains Matematik UMPSA, 2023)
On 19 May 2023, Centre for Mathematical Sciences has been successfully organised the third Monthly Mathematical Colloquium in 2023.